BAHASA IKLAN LAYANAN MASYARAKAT DAN IMPLIKASINYA TERHADAP PEMBELAJARAN MENULIS PERSUASI DI SMP - Edi Sukamto; Nurlaksana Eko Rusminto; Ni Nyoman Wetty (FKIP Universitas Lampung, 2013)
The problem in this research is the language from public service Ad and its implication for the the learning of persuasion writing at SMP. This research has a purpose to describe language in public service Ad masyarakat such as, the use of spelling, and the effectiveness of sentence, and then the implication for the learning of persuasion writing at SMP. The research design which is used is qualitative descriptive, that is the procedure of problem solving by explaining the research objective based on the facts which is happening. The data source in this research is the public service Ad which is at the jl. Zainal abiding pagar alam kedaton, Bandar lampung. Form the result of observation, this research get eleven public service Ads from the eight public service Ads with the different topic and theme. From the result of this research, there are eleven public services Ads in the Jl. Zainal Abidin Pagar Alam, Kedaton, Bandar Lampung which has interesting phenomenom in the using of spelling especially in the using of punctuation (.), (,) and the use of capital words. Beside of that diction that is used in the public service Ad at the jl zainal abiding pagar alam, kedaton Bandar lampung, there are seven public servis Ads which means connotation and there are five which means denotation, and the effectiveness sentence in the public service Ad put on the similarity between the kind of sentence which is used and the message that will be delivered.Key words : public service, language public services, public service ads